Separating Uncertainty from Heterogeneity in Life Cycle Earnings - Flavio Cunha; James Joseph Heckman; Salvador Navarro (Institute for the Study of Labor (IZA), 2004)
This paper develops and applies a method for decomposing cross section variability of earnings into components that are forecastable at the time students decide to go to college (heterogeneity) and components that are unforecastable. About 60% of variability in returns to schooling is forecastable. This has important implications for using measured variability to price risk and predict college attendance.
Keywords: I21; C33; D84; 330; uncertainty; lifecycle earnings; schooling; heterogeneity; counterfactuals; Lebenseinkommen; Lebenszyklus; Bildungsverhalten; Bildungsertrag; Schätzung; Vereinigte Staaten